A real‐world comparison of cisplatin vs cetuximab used concurrently with radiation in the treatment of locally advanced oropharyngeal carcinoma. Issue 1 (19th September 2020) - Fung, Andrea S.; Afzal, Arfan Raheen; Banerjee, Robyn; Debenham, Brock; Hao, Desiree
Abstract: Background: This population‐based retrospective study compares the efficacy of cisplatin (cis‐RT) vs cetuximab (cetux‐RT) with concurrent radiation as definitive treatment in patients with oropharyngeal carcinoma (OPC). Methods: Patients with OPC treated in Alberta with cis‐RT or cetux‐RT between 2006 and 2016 were evaluated. Median disease‐free survival (DFS) and overall survival (OS) were assessed using the Kaplan‐Meier method. Multivariable analysis (MVA) was completed with a Cox proportional hazards model. Results: Among 546 patients with OPC, 431 (78.9%) received cis‐RT and 115 (21.1%) cetux‐RT. Patients treated with cetux‐RT were more likely to develop a recurrence after treatment compared to cis‐RT (25% vs 15%, P = .01). On MVA, current smoking, human papillomavirus (HPV)‐negative status, higher Charlson comorbidity index (CCI), T‐stage, and cetux‐RT predicted for worse DFS and OS. Outcomes in older patients with a higher CCI still favored cis‐RT. Conclusions: Our data reaffirm results from randomized studies showing better survival outcomes with cis‐RT compared to cetux‐RT even among those who are >65 with CCI ≥3.